LABORATORY DIAGNOSIS OF THALASSEMIA - Isakulova Muhabbat Mardanovna; Ibragimova Nadiya Sabirovna; Anvarhonova Muhtasarhon Asrorhon kizi (TADQIQOTLAR.UZ, 2024)
Annotation. Laboratory diagnosis of thalassemia occupies an important place in the modern approach to the treatment and prevention of this hereditary disease. Thalassemia, a group of disorders involving hemoglobin synthesis, can cause serious complications including anemia, cardiovascular problems and growth retardation. Early diagnosis is critical to selecting optimal treatment methods and monitoring the patient’s condition.